PENDIDIKAN KARAKTER DALAM LARANGAN MENYEMBELIH SAPI (Menelisik Filosofi Ajaran Sunan Kudus) - Mahlail Syakur (Jurnal Progress)
Islam as a part of the social system comes with a mission as rahmah lil-‘alamin to take part in nation-building. On the other sides Indonesia is a multicultural country where Islam is one of the subsystems. Therefore, Islam should be introduced as the potential for an inclusive, democratic and pluralist. Sunan Kudus spreads Islam by way of acculturation traditions and local culture because at that time the majority of the population is Hindu Holy.